(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Fabric hand is defined as the human tactile sensory response towards fabric, which involves not only physical but also physiological, perceptional and social factors. Fabric hand is one of the most important characteristic of a fabric. This paper discusses the relationship between technical features of high counts and high density fabrics and their hand evaluation. 13 samples of high counts and high density fabrics were selected to be measured by the Kawabata Evaluation System (KES). The range of the mechanical properties of high counts and high density fabrics was given. Using factor analysis with quartimax rotation, 5 factors model was generated. The relationship between the 5 factors and the technical features was shown by using correlation analysis. The study in this paper can offer references for the quality control of high counts and high density fabric design.